Níveis críticos e avaliação nutricional da bananeira prata-anã cultivada no norte de Minas Gerais - Iran Scarcella de Carvalho Junior (2017)
Banana stands out in the world production of fruit, occupying the first position, with a production of 106.5 million tons, being that Brazil produces seven million tons, with a participation of 6.9% in this total. The northern region of Minas Gerais produces 50.6% of state banana production and it occupies a prominent national position in this activity. It has great socioeconomic importance for the region, generating thousands of jobs. In this way, the evaluation of the nutritional status of the culture and the safe interpretation of the results becomes determinant to reach good results. It was proposed in this work the definition of critical levels in soil and plant, and the nutritional evaluation for banana crop, cv. Prata-Anã, using the reduced normal distribution method, grown in the northern region of Minas Gerais. Were used the productivity data (Prod.) and nutrient contents in the soil and in the reference leaf of 14 commercial areas of banana production in the years of 2013, 2014 and 2015. According to the reduced normal distribution method, it was estimated the relationship between Prod. and Q (Q = Prod. / Ni), where Ni is the nutrient content that one hopes to find the critical level. The critical level was obtained by the equation NCi = (1.281552s1 + x1) / (1.281552s2 + x2), where x1 and s1 are the arithmetic mean and standard deviation of P and x2 and s2, the mean and the standard deviation of Q. The critical levels of soil chemical attributes obtained for irrigated banana areas were 6.6 for pH, 45.1 mg dm-3 for P, 132.9 mg dm-3 for K, 3.9 cmolc Dm-3 for Ca and 1.3 cmolc dm-3 for Mg. Already for the leaf contents were of 23.8; 1.7; 35.6; 6.6; 2.9 and 1.7 g kg-1 for N, P, K, Ca, Mg and S, respectively, and 62.3; 17.9; 280.3; 12.3 and 7.1 mg kg -1 for Fe, Zn, Mn, B and Cu, respectively. In the areas of low productivities the greatest soil deficiencies were K and Ca in the year 2013, P and Ca in the year 2014 and again P and Ca in the year 2015. Already for the foliar contents observed a greater deficiency for the N in the year 2014 and K in the year 2015.